Social Injustice in the Industrial Revolution 4.0 - Niravita, Aprila (Universitas Negeri Semarang, 2020)
SOCIAL JUSTICE issues can occur in relation to practically any aspect of society where inequality can arise as a result of unjust prejudices or policies. Social justice issues can be delineated into two categories, although they are often co-dependent: Inter-Social Treatment and Unequal Government Regulation.